Turn It Off: An Action Research Study of Top Management Influence on Energy Conservation in the Workplace - Russell, Sally V.; Evans, Alice; Fielding, Kelly S.; Hill, Christopher (Frontiers in Psychology, 2016)
This paper reports the results of an intervention study that aimed to encourage workplace energy conservation behavior by office-based employees. Taking a co-production approach we worked with the participating organization to design and implement an intervention that used the influence of top management commitment and prompts to encourage workplace energy reduction. Whilst past research has shown top management is related to workplace pro-environmental behavior, this study extends this work by examining a field-based intervention over a longitudinal period. The efficacy of the intervention was measured using observational and self-reported data over a period of six months. Results showed that there were significant changes in objective and self-reported energy conservation behavior, perceived top management commitment, organizational culture, norms, and knowledge regarding energy conservation behavior over the course of the study. The findings also demonstrated that the intervention was most successful for those behaviors where employees have individual responsibility. Implications for future research and practice are discussed.